2004
DOI: 10.1074/jbc.m401238200
|View full text |Cite
|
Sign up to set email alerts
|

Mammalian Target of Rapamycin Positively Regulates Collagen Type I Production via a Phosphatidylinositol 3-Kinase-independent Pathway

Abstract: The mammalian target of rapamycin (mTOR) is a multifunctional protein involved in the regulation of cell growth, proliferation, and differentiation. The goal of this study was to determine the role of mTOR in type I collagen regulation. The pharmacological inhibitor of phosphatidylinositol (PI) 3-kinase, LY294002, significantly inhibited collagen type I protein and mRNA levels. The effects of LY294002 were more pronounced on the collagen ␣1(I) chain, which was inhibited at the transcriptional and mRNA stabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
84
0
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(92 citation statements)
references
References 73 publications
(68 reference statements)
7
84
0
1
Order By: Relevance
“…In our sister paper, 28 we also showed rapamycin potentiates CCN2 expression in alveolar epithelial cells by PI3K pathway. Furthermore, we and others also showed that while rapamycin downregulated collagen mRNA or protein expression in normal human fibroblast, 18,29 it could even facilitate the expression of collagen I α1 mRNA in the presence of TGF-β1 (unpublished preliminary data), indicating that the downstream effectors are differentially modulated by mTORC when inhibited by rapamycin and may be highly cell specific. The overall effect of rapamycin on lung fibrosis relies on the balance of the controversial functions on lung structural cells.…”
Section: Discussionmentioning
confidence: 99%
“…In our sister paper, 28 we also showed rapamycin potentiates CCN2 expression in alveolar epithelial cells by PI3K pathway. Furthermore, we and others also showed that while rapamycin downregulated collagen mRNA or protein expression in normal human fibroblast, 18,29 it could even facilitate the expression of collagen I α1 mRNA in the presence of TGF-β1 (unpublished preliminary data), indicating that the downstream effectors are differentially modulated by mTORC when inhibited by rapamycin and may be highly cell specific. The overall effect of rapamycin on lung fibrosis relies on the balance of the controversial functions on lung structural cells.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, expression of mTOR was recently advanced as a mediator of fibrosis in scleroderma (17). Notably, the HIF-1␣ and mTOR were localized to regions in which we have previously observed TGF␤ staining and nuclear translocation of SMAD2 (3).…”
Section: Discussionmentioning
confidence: 86%
“…Despite of the IL-3 encoding mRNA, destabilizing effects by rapamycin have furthermore been described for other mRNAs including those coding for collagen type 1 [32] and collagen type 3A1 [28] as well as cyclin D 3 mRNA [30]. Similar to IL-3 mRNA, the destabilizing effect of rapamycin on cyclin D 3 mRNA is attributed to two canonical AREs in the 3´-UTR of an mRNA [33].…”
Section: Discussionmentioning
confidence: 92%